2015
DOI: 10.1111/1750-3841.12743
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay‐Based Isolation and Identification of Phenolics from Sweet Cherry That Promote Active Glucose Consumption by HepG2 Cells

Abstract: A variety of phenolics had been found to be functional in promoting cellular glucose consumption that is important for blood glucose regulation. Sweet cherry (Prunus avium) is rich in such kinds of phenolics, including hydrocinnamic acids, anthocyanins, flavonols, and flavan-3-ols. Furthermore, a sweet cherry phenolics-rich extract (PRE) was found to be effective in promoting HepG2 glucose consumption. Seventeen components were preliminarily identified by HPLC-ESI-MS, including 9 hydrocinnamic acids, 4 anthocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The antidiabetic properties of sweet cherries are already known [ 7 , 29 , 30 ]. Lachin [ 30 ] reported that diabetic rats fed with 200 mg of cherry extract per kg of body weight for 30 days showed reduced blood glucose and urinary microalbumin levels, proving that the ingestion of these fruits can protect pancreatic β-cells and retard glucose absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antidiabetic properties of sweet cherries are already known [ 7 , 29 , 30 ]. Lachin [ 30 ] reported that diabetic rats fed with 200 mg of cherry extract per kg of body weight for 30 days showed reduced blood glucose and urinary microalbumin levels, proving that the ingestion of these fruits can protect pancreatic β-cells and retard glucose absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Lachin [ 30 ] reported that diabetic rats fed with 200 mg of cherry extract per kg of body weight for 30 days showed reduced blood glucose and urinary microalbumin levels, proving that the ingestion of these fruits can protect pancreatic β-cells and retard glucose absorption. Besides, Cao et al [ 29 ] revealed that fractionated extracts of Black Pearl sweet cherry cultivar rich in anthocyanins, hydroxycinnamic acids, and flavonols also demonstrated antidiabetic properties by promoting cellular glucose consumption in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…As referred above, it was already reported that sweet cherries have antidiabetic properties [7,29,30]. Hereupon, human colorectal adenocarcinoma Caco-2 cells were selected given two reasons: (i) they are a model of the intestinal epithelium, since, after differentiation, they form monolayers, that reproduce several characteristics of intestinal epithelial cells (e.g.…”
Section: Effect Of Sweet Cherry Extracts In Caco-2 Cell Viabilitymentioning
confidence: 99%
“…[4][5][6] Insulin resistance, a state of reduced response to insulin, is a pivotal pathological feature of T2DM and the primary organs responsive to insulin are liver, skeletal muscle and adipose tissue. 7,8 Among these tissues, 90% of the endogenous glucose production occurs in the liver, and increased hepatic gluconeogenesis seems to be the probable cause of fasting hyperglycemia, which eventually exacerbates insulin resistance. 9,10 Thus, to ameliorate hepatic insulin resistance and increase sensitivity, various synthetic pharmaceuticals have already been in the market.…”
Section: Introductionmentioning
confidence: 99%